Pengaruh Pelatihan Keterampilan Sosial untuk Meningkatkan Relasi - Faizah Kumala; P Purwati; Astiwi Kurniati (Prosiding University Research Colloquium, 2022)
Purpose of the research to find out the effect of social skills training to improve the social relations of the 9th grade students of SMP Plus Ihya'ul Ulum Muntilan.This research is the true experimental research with the pretest posttest control group design method. The subjects of the research is chosen by random sampling method. The collecting data method is using social relations questionnaire. The prerequisite analysis test is consist of normality test and homogeneity test. Data analysis is using One Way Anova Parametric Statistical analysis with the help of the SPSS 24.00 windows program. The results of the research indicate that social skills training ia affected toward the student social relations with the evidenced from the parametric One Way Anova. Test of the experimental group with probability signification of 0.005 < 0.05. Based on the analysis and study, there is a difference of the social relations questionnaire average point between the experimental group and the control group amount 10% for the experimental group and 2% for control group. Based on the research result can concluded that there is an effect of the social skills training to increase social relations.